Copper Recovery from Scrap Electrical Cables based on an Environmentally Sustainable Gravity Separation Technique - Syed, Naveed ul Hasan; Khan, Naseer Ahmed; Ahmad, Naveed; Ahmad, Farooq; Alsayer, Ibrahim Ali; Altuwair, Ibrahim Abdullah; Ahmad, Syed Afzal; Zaheer, Rayan; Khan, Reyan; Jan, Shahzad (Engineering, Technology & Applied Science Research, 2025)
The aim of this study is to recover copper from scrap cable wires through a sustainable gravity separation technique. Initially, the scrap wires were shredded in such a way, that the plastic on them was completely removed. The shredded mixture of the copper and plastic pieces was poured on a shaking table, where separation of copper and plastic was caused. The copper was collected in the concentrate zone and the plastic pieces were collected in the tailings zone. The study also examines the influence of the shaking table inclination at 1º, 3º, and 5º, and that of the wash water flow rate, ranging from 9 to 34.70 ml/sec, on the stratification of the copper plastic mixture. It was found that increasing both the shaking table inclination and the wash water flow rate improved copper recovery. However, at the maximum angle of 5º and wash water flow rate of 34.70 ml/sec, the recovered copper grade decreased due to the plastic pieces’ contamination. The most favorable results were obtained at the shaking table inclination of 3º and wash water flow rate of 20.50 ml/sec, which resulted in a copper concentrate with a copper recovery of 93.5% and a copper grade of 98%. Additionally, it was found that wash water can be recycled, which, in a commercial setting, could save up to 590 L of fresh water per 8 hours.